Health and Beauty : A Book for Girls - Foley, Elizabeth; Cocker, Edith A. (London : The Health & Cleanliness Council)
1939-10 1939 1930s 27 pages ; illustrations THE MODERN WAY Games and sports of all kinds, especially outdoor ones, are very good for health and beauty. They provide a great variety of movements, and while promoting grace of body, help to keep you fit, so you should try to keep them up when you leave school. To avoid getting out of condition, you could join a physical culture club; but, in any case, you should certainly devote a short time daily to systematic physical exercise. By doing exercises regularly, you will look and feel better, breathe and digest your food better, and have a better figure. Remember that the real object of physical culture is to gain and keep health rather than win matches and prizes. Studying hard for exams, or learning a new job is exhausting; if you are still growing you may have to "go slow" temporarily with strenuous games. Suitable exercises, however, will build up and render more shapely any part of the body that needs it. Try simple arm and leg exercises to music (gramophone or wireless). You can do this at home. Exercise every day, in the open air if possible, or in front of an open window, wearing loose, light clothing — a swim-suit is ideal — and always take a bath, or wash all over, after exercise. The more you exercise your body, the greater the need for strict personal cleanliness. The comfort and enjoyment of a thorough wash after a long and tiring day in the open, or after dancing in a hot, crowded room, must be experienced to be believed. You cannot be too fastidious about bathing the body. Daintiness is the most attractive quality a girl can possess when wearing her prettiest dress, as on all other occasions. There is health value in a "good sweat," which is one of Nature's ways of getting rid of waste products. Hence the need for a warm bath after exercise. Bathing the body with plenty of water, and using a good soap in removing the unpleasant stickiness from your skin, puts the finishing touch to your enjoyment — a feeling of daintiness — and helps your health by cleanliness. 18 177/5/8/4